Effect of Material ConductivityThermalto Sea Water Evaporation in Solar Desalination - Oktarina Heriyani; Mugisidi Mugisidi; Hamdi Faturohman (International Conference on Coastal and Delta Areas, 2017)
Sea desalination technology with solar energy is very suitable to be utilized in Indonesia to produce fresh water with low production costs. In order to speed up the evaporation process, a suitable material is needed to be used as a seawater pan. Therefore, the purpose of this study is to determine the appropriate material to be used as a place of sea water. This research uses trapezium bowl with aluminium, copper, rubber, and glass material with surface area of 31.5 cm2 and 250 ml of water. Data collection from 10:00 am until 14:00 pm for five days. Environmental, material, and water temperatures are measured hourly. In high material conductivity such as copper (319.25 W/m.°C) and aluminium (16.95 W/m°C), the evaporation was 33.96 and 30.48 ml. While rubber (0.13 W/m°C) and glass (0.15 W/m°C) which had lower conductivity, also have lower evaporation, that was 27,68 and 27,83 ml. Thus, in desalination process by using solar heat, conductivity of container material affected the amount of water that evaporates. The higher the thermal conductivity value of the material then the volume of evaporated water would also be greater. Keywords: keywords desalination, evaporation, sea, water, solar